PRODUCTION OF CATHODES, TARGETS OF HIGH FREQUENCY OF CHEMICALLY ACTIVE METALS - V. N. Alehnovich; V. V. Alehnovich (Литьë и металлургия)
The production of cathodes, accumulation electrodes of high frequency of chemically active metals is considered.